Dual-linker gold nanoparticles as adjuvanting carriers for multivalent display of recombinant influenza hemagglutinin trimers and flagellin improve the immunological responses in vivo and in vitro - Wang C (Dove Medical Press, 2017)
Chao Wang, Wandi Zhu, Bao-Zhong Wang Center for Inflammation, Immunity and Infection, Georgia State University Institute for Biomedical Sciences, Atlanta, GA, USA Abstract: Vaccination is the most cost-effective means of infectious disease control. Although current influenza vaccines are effective in battling closely matched strains, such vaccines have major limitations such as the requirement to produce new vaccines every season, an egg-dependent production system, long production periods, uncertainty in matching the vaccine to circulating strains, and the inability to react to new influenza pandemics resulting from genetic drift or shift. To overcome the intrinsic limitations of the conventional influenza vaccine, we have designed dual-linker gold nanoparticles (AuNPs) conjugated with both recombinant trimetric A/Aichi/2/68 (H3N2), hemagglutinin (HA) and TLR5 agonist flagellin (FliC) as a novel vaccine approach. Click chemistry and metal-chelating reactions were used to couple the two proteins. The conjugated proteins were found to possess high coupling specificity, high stability in harsh environments, high conjugation efficiency, and the ability to keep the appropriate protein conformations for immunogenicity and immunostimulation. Both AuNPs-HA/FliC and AuNPs-HA formulations induced higher levels of antibody responses than a mixture of soluble HA and FliC proteins when administered via a single intranasal immunization in mice. To further investigate the adjuvancy of these nanoparticles, in vitro experiments were conducted in both the JAWS II dendritic cell (DC) line and bone marrow-derived DC (BMDC) models. The results showed that dual-conjugated AuNPs were rapidly targeted and taken up by DCs. Consequently, DCs were induced toward maturation, as demonstrated by high levels of cytokine secretions and membrane costimulatory molecule expression. T cell proliferation was observed when splenic T cells were cocultured with AuNPs-HA/FliC-primed BMDCs. These results suggest that dual-conjugated AuNPs are effective at simultaneously displaying antigens and adjuvants in an oriented, multivalent format and can promote a strong immune response by activating DCs and T cells. Keywords: adjuvant, co-delivery, dendritic cells, influenza vaccine, gold nanoparticle